Child Nutrition, Economic Growth, and the Provision of Health Care Services in Vietnam in the 1990s - Glewwe, Paul (World Bank, Washington, DC, 2013)
Vietnam's rapid economic growth in the 1990s greatly increased the incomes of Vietnamese households, which led to a dramatic decline in poverty. Over the same period, child malnutrition rates in Vietnam, as measured by low height for age in children under 5, fell from 50 percent in 1992-93 to 34 percent in 1997-98. Disparities exist, however, between different regions, urban and rural areas, ethnicities, and income quintiles. This dramatic improvement in child nutrition during a time of high economic growth suggests that the nutritional improvements are due to higher household incomes. The authors investigate whether this causal hypothesis is true by estimating the impact of household income growth on children's nutritional status in Vietnam. Different estimation methods applied to the 1992-93 and 1997-98 Vietnam Living Standards Survey data find that growth in household expenditures accounts for only a small proportion of the improvements in children's nutritional status. The authors use data on local health facilities to investigate the role that they may have played in raising children's nutritional status in Vietnam.